Activity of Pembrolizumab in Recurrent Cervical Cancer: Case Series and Review of Published Data. Issue 6 (1st June 2018) - Kranawetter, Marlene; Röhrich, Sebastian; Müllauer, Leonhard; Obermair, Helena; Reinthaller, Alexander; Grimm, Christoph; Sturdza, Alina; Köstler, Wolfgang J.; Polterauer, Stephan
Abstract : Objectives: Recent data support the use of pembrolizumab in cervical cancer. The aim of this study was to investigate pembrolizumab in heavily pretreated patients with recurrent cervical cancer. Methods: Data from consecutive patients treated with pembrolizumab at a single academic institution were assessed. Programmed cell death ligand 1 (PD-L1) status and microsatellite instability were assessed from tumor samples. Irrespective of PD-L1 expression status, pembrolizumab was administered at fixed dose of 200 mg intravenously every 3 weeks. Treatment response was evaluated by computed tomography, using iRECIST (2017) criteria. Descriptive statistics were performed. Results from previous publications were summarized. Results: In total, 11 heavily pretreated patients with recurrent cervical cancer received pembrolizumab. Of these, 2 (18%) patients showed partial response and 2 (18%) patients showed disease stabilization on computed tomography, resulting in a clinical benefit rate of 36%. These 4 patients are still on treatment and durable antitumor activity of up to 52 weeks was observed. Treatment was generally well tolerated with 1 patient showing dose-limiting toxicity. Median overall survival was 26 (3–53) weeks, and a 6-month overall survival rate of 65% was observed. Of the 5 patients with high PD-L1 expression, 3 showed response to treatment. Conclusions: Pembrolizumab shows promising activity in heavily pretreated patients with recurrent cervical cancer in a real-life clinical setting. Treatment was generally well tolerated, and adverse effects were manageable. Growing evidence supports the use of pembrolizumab in this group of patients.